E-011 SOFIA Distal Access Catheter for Endovascular Treatment of Acute Ischemic Stroke Using Combined Mechanical and Aspiration Thrombectomy. (29th July 2016) - Wong, J; Do, H; Telischak, N; Moraff, A; Marks, M; Dodd, R; Heit, J
Abstract : Introduction: Mechanical thrombectomy with stent retrievers is superior to medical management in acute ischemic stroke due to large vessel occlusion (LVO). The Direct Aspiration First Pass (ADAPT) and combined mechanical/aspiration thrombectomy (Solumbra) techniques are used in endovascular stroke treatment; these techniques require an intermediate catheter for suction at the clot interface. SOFIA (Soft torqueable catheter Optimized For Intracranial Access) is a single lumen flexible catheter with coil and braid reinforcement developed for intracranial use. We describe our initial experience with SOFIA in acute stroke intervention and evaluate its efficacy and safety. Methods: Our institutional review board approved this study. We retrospectively identified all patients undergoing endovascular stroke therapy using SOFIA from our database. Patient demographic data, stroke presentation, treatment details, and complications were recorded from the medical record. The primary outcome was successful revascularization (TICI IIb or III) and the number of passes for revascularization. Secondary outcome measures were complication rates and NIHSS score on discharge. Results: 33 patients (20 females, 13 males) were treated for LVO using the SOFIA catheter. Mean patient age was 71.9 years. Intravenous tPA was administered in 22 patients (67%). Vessel occlusion predominantly affected the anterior circulation (10 left sided and 21 right sided) and involved the ICA terminus (5 patients, 15.2%), M1 (16 patients, 48.5%) and M2 (8 patients, 24.2%) segments. 4 patients (12.1%) had posterior circulation strokes. Mean NIHSS was 14.2 (95% CI 12.3–16.2) on presentation and 7.8 (95% CI 4.9–10.6) on discharge. The Solumbra technique was used in 31 patients (94%), ADAPT in one patient (3%), and intra-arterial thrombolysis in one patient (3%). Successful revascularization was achieved in 31 patients (94%), including TICI III in 16 patients (48.5%). The average number of passes to reperfusion was 1.6 (95% CI 1.3–2.0). Mean time to reperfusion was 47 minutes. Symptomatic intraparenchymal hemorrhage following reperfusion occurred in 2 patients (6%). Procedural complications occurred in 4 patients (12%), including dissection, microwire perforation, and hemorrhage into a pre-existing intracranial tumor; all complications were unrelated to the SOFIA. Mortality was 21.2% secondary to failed revascularization, hemorrhagic transformation, and severe baseline medical disease. Conclusion: SOFIA is a safe and effective intermediate catheter for mechanical and aspiration thrombectomy in acute stroke intervention. In conjunction with stent retrievers and suction aspiration technique, successful revascularization was 94%, with average number of passes of 1.6. There were no complications directly attributable to the use of SOFIA. Disclosures: J. Wong: None. H. Do: 2; C; MicroVention, Inc. N. Telischak: None. A. Moraff: None. M. Marks: None. R. Dodd: None. J. Heit: 2; C; MicroVention, Inc.